An improved reversibly dimerizing mutant of the FK506-binding protein FKBP. Issue 3 (2nd July 2016) - Barrero, Juan J.; Papanikou, Effrosyni; Casler, Jason C.; Day, Kasey J.; Glick, Benjamin S.
ABSTRACT: FK506-binding protein (FKBP) is a monomer that binds to FK506, rapamycin, and related ligands. The F36M substitution, in which Phe36 in the ligand-binding pocket is changed to Met, leads to formation of antiparallel FKBP dimers, which can be dissociated into monomers by ligand binding. This FKBP(M) mutant has been employed in the mammalian secretory pathway to generate aggregates that can be dissolved by ligand addition to create cargo waves. However, when testing this approach in yeast, we found that dissolution of FKBP(M) aggregates was inefficient. An improved reversibly dimerizing FKBP formed aggregates that dissolved more readily. This FKBP(L, V) mutant carries the F36L mutation, which increases the affinity of ligand binding, and the I90V mutation, which accelerates ligand-induced dissociation of the dimers. The FKBP(L, V) mutant expands the utility of reversibly dimerizing FKBP.